Third grave dead ahead - Jones, Darynda (New York : St. Martin's Press, 2012)
"Paranormal private eye. Grim reaper extraordinaire. Whatever. Charley Davidson is back! And she's drinking copious amounts of caffeine to stay awake because, every time she closes her eyes, she sees him: Reyes Farrow, the parthuman, part-supermodel son of Satan. Yes, she did imprison him for all eternity, but come on. How is she supposed to solve a missing persons case, deal with an ego-driven doctor, calm her curmudgeonly dad, and take on a motorcycle gang hellbent on murder when the devil's son just won't give up?"--
"A novel"--Cover.
Keywords: Davidson, Charley -- (Fictitious character) -- Fiction; FICTION / Mystery & Detective / Women Sleuths; FICTION / Fantasy / Paranormal; Occult fiction; Mystery fiction